Performance Of State Civil Apparatus At The Liaison Agency Of Gorontalo Province In Jakarta - Claudhia F. Laboro; Hadi Prabowo; Andi Masrich (Sean Institute, 2024)
The Gorontalo Provincial Liaison Agency in Jakarta as an extension of the Gorontalo Provincial Government in the Center of the National Capital, was formed based on Gorontalo Governor Regulation Number 81 of 2016 concerning the Position, Organizational Structure, Duties and Functions and Work Procedures of the Liaison Agency. The Liaison Agency is known as a Regional Apparatus Organization with the task of Facilitating Leadership Services because what is seen and considered optimal in achieving its performance is the Institutional Relations Facilitation Sub Sector. Meanwhile, the implementation of the duties of the Promotion and Information Facilitation Sub-Sector as well as the Administration Sub-Section which is part of the operational process of governance of the Gorontalo Province Liaison Agency in Jakarta, is considered not to be effective and efficient in achieving the assigned performance. The aim of this research is to analyze and describe the performance of the State Civil Apparatus at the Gorontalo Province Liaison Agency in Jakarta. This study uses a descriptive research design with qualitative methods. Informants were obtained through purposive and snowball sampling techniques using the Miles and Huberman Model Interactive data analysis as a performance analysis tool based on theory according to T.R Mitchell (1978:343) in (Sedarmayanti, 2001:51) which has 5 (five) Employee Performance Indicators, namely Quality Work, Punctuality, Initiative, Ability and communication. The results of this study show that the performance of ASN at the Gorontalo Province Liaison Agency in Jakarta based on the implementation of Job Analysis and Workload Analysis given to each ASN can be completed well. Looking at the results of this study, in order to optimize and efficiently carry out tasks by ASN Gorontalo Province Liaison Agency in Jakarta, through appreciation and support from leadership in maintaining ASN work motivation, fulfilling work facilities and infrastructure, improving ASN welfare, providing equal opportunities to It is hoped that every ASN can develop and improve their abilities through education and training as well as promotions.